Pengaruh Komite Audit dan Reputasi Kantor Akuntan Publik (KAP) terhadap Integritas Laporan Keuangan dengan Corporate Governance sebagai Pemoderasi - Darsono, Rivianty Rafifah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to examine the influence of the audit committee and the public accounting firm's reputation on the integrity of financial reports, with corporate governance as a moderator. In this study, corporate governance is represented by independent commissioners and institutional ownership. The sample used in this research consists of 60 companies, including 20 in the financial sector listed on the Indonesia Stock Exchange during the period 2020-2023. The data for this research is derived from the companies' annual reports. The data was tested and analyzed using multiple linear regression analysis and moderated regression analysis (MRA) conducted using SPSS 26 software. The research found that the audit committee and the reputation of the public accounting firm collectively influence the integrity of financial reports. The reputation of the public accounting firm influences the integrity of financial reports, and institutional ownership can moderate the reputation of the public accounting firm's influence on the integrity of financial reports. The audit committee does not partially affect the integrity of financial reports. Independent commissioners and institutional ownership cannot moderate the influence of the audit committee on the integrity of financial reports. Independent commissioners cannot moderate the influence of the public accounting firm's reputation on the integrity of financial reports.